Awareness of the association between periodontal disease and adverse pregnancy outcome among the female population in Benghazi city-Libya - Werfully, Salma Mahfoud; Al Ghazal, Logien (Libyan Journal of Dentistry, 2018)
Objectives: Chronic periodontitis is initiated and sustained by bacterial plaque, but host defence mechanism plays an integral role in it is pathogenesis. Periodontal disease (PD) is affecting more than 23% of women between the age of 30 and 54 years. Female sex hormones – progesterone and estrogen- vary in their levels throughout a women’s life, depending on which phase she is at (Puberty, Pregnancy or menopause). Progesterone has a stronger influence as an inflammatory mediator. The mechanism Periodontitis is probably one of the pathologic insults to normal gestational function and causes adverse outcomes (APOs). Design: A Cross-sectional survey was conducted among female sample in Benghazi city. A structured interview questionnaire was used in this study. Results: Two hundred and nine female their age ranged between 20 to 60 years were participated in the study. 38.9% of the participating females have known that there is an association between periodontal disease PD and general health. But only 31.4% knew that PD increases during pregnancy (younger age group). Despite that 43.3% of the sample was aware about the symptoms of PD, 50.2% did not visit a dentist for more than one year and only 14.8% visited a dentist when there is pain or discomfort. Whereas, 88% of the sample had no idea that there could be an association between PD and adverse pregnancy outcome. Conclusion: There was a deficiency in the knowledge of female population about periodontal disease in relation to hormonal changes and the adverse effects on pregnancy.